Linguo culturological Analysis of the Language of Advertising in The American English Language - Gazizova Farida Samigulovna; Samatova Gulnoza (Genius Journals, 2023)
This article is devoted to the study of advertising discourse in American English. Advertising is a mirror of a country’s culture, its mentality and national character, which reflects all socio-cultural phenomena. The study reveals not only the linguistic and cultural features of advertising slogans, but also conducts their linguistic and stylistic analysis in order to identify the cultural characteristics of American society.
Keywords: Linguacultural; advertising; national character; advertising slogan